Antimicrobial and Cytotoxic Effects of Cannabinoids: An Updated Review with Future Perspectives and Current Challenges - Mansab Ali Saleemi; Noorfatimah Yahaya; Nur Nadhirah Mohamad Zain; Muggundha Raoov; Yoke Keong Yong; Nurul Shahfiza Noor; Vuanghao Lim (MDPI AG, 2022)
The development of new antibiotics is urgently needed to combat the threat of bacterial resistance. New classes of compounds that have novel properties are urgently needed for the development of effective antimicrobial agents. The extract of Cannabis sativa L. has been used to treat multiple ailments since ancient times. Its bioactivity is largely attributed to the cannabinoids found in its plant. Researchers are currently searching for new anti-infective agents that can treat various infections. Although its phytocannabinoid ingredients have a wide range of medical benefits beyond the treatment of infections, they are primarily associated to psychotropic effects. Different cannabinoids have been demonstrated to be helpful against harmful bacteria, including Gram-positive bacteria. Moreover, combination therapy involving the use of different antibiotics has shown synergism and broad-spectrum activity. The purpose of this review is to gather current data on the actions of Cannabis sativa (C. sativa) extracts and its primary constituents such as terpenes and cannabinoids towards pathogens in order to determine their antimicrobial properties and cytotoxic effects together with current challenges and future perspectives in biomedical application.